NEW DATA ON THE DISTRIBUTION OF LEPIDOPTERA IN MONTENEGRO, WITH A REVIEW OF ABERRANT FORMS - Jakšić, Predrag; King, Andrew (Bulletin of Natural Sciences Research, 2021)
During the three-year period of investigations, species from the families Depressariidae Meyrick, 1883, Pyralidae Latreille, 1809, Crambidae Latreille, 1810, Lycaenidae Leach, 1815, Nymphalidae Rafinesque, 1815, Geometridae Leach, 1815 and Erebidae Leach, 1815 were investigated. Investigations were carried out in 20 localities, distributed throughout the entire territory of Montenegro. Two species are listed for Montenegro for the first time: Hypoxystis pluviaria (Fabricius, 1787) and Aspitates ochrearia (Rossi, 1794).